2011
DOI: 10.4103/0970-9371.86343
|View full text |Cite
|
Sign up to set email alerts
|

Cytological pattern of cervical papanicolaou smear in eastern region of Saudi Arabia

Abstract: Background:Cancer of the cervix has been considered as one of the preventable cancers. This study is the first published research addressing the screening of cancer of the cervix in the eastern region of Saudi Arabia.Aim:This study aims to detect the prevalence of abnormal epithelial changes and its types in the eastern region of Saudi Arabia.Settings and Study Design:A retrospective study was designed to evaluate all previously conducted cervical smears examined at a secondary care maternity hospital in Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 14 publications
(14 reference statements)
6
15
4
Order By: Relevance
“…Also at variance with our study is a normal smear rate of 94.5% in USA, which helps to explain that routine screening and other preventive measures when implemented, helps to achieve great results. 14 The rates of inflammatory smear in Saudi Arabia 12 and india 13 are high (48.3% and 57.4%) when compared to that in our study (14.6%), but the rate of premalignant lesion in our study may be a guide to the fact that other co-carcinogens apart from infections may abound in our environment and may be responsible for the high rate of premalignant lesions.…”
Section: Discussioncontrasting
confidence: 42%
“…Also at variance with our study is a normal smear rate of 94.5% in USA, which helps to explain that routine screening and other preventive measures when implemented, helps to achieve great results. 14 The rates of inflammatory smear in Saudi Arabia 12 and india 13 are high (48.3% and 57.4%) when compared to that in our study (14.6%), but the rate of premalignant lesion in our study may be a guide to the fact that other co-carcinogens apart from infections may abound in our environment and may be responsible for the high rate of premalignant lesions.…”
Section: Discussioncontrasting
confidence: 42%
“…The prevalence rates published in previous studies ranged from 1.66-7.9% [22][23][24]. Studies done on the prevalence of epithelial cell abnormality have shown 4.3% in Kuwait [25] 7.9% in South west Saudi Arabia [19] and 4.95% in Eastern Saudi Arabia [26]. These studies showed an overall prevalence of the epithelial abnormalities similar to the current study.…”
Section: Discussionsupporting
confidence: 85%
“…15 Study conducted by Balaha et al mean age of 45 years for ASCUS, 35.8 years for HSIL. 16 While Gupta et al showed predominance of ASCUS, LSIL in less than 40 years and Carcinoma in >40 years age group. 8 Study by Saraiya U et al found mean age of 32.5 years, 37.5 years and 44.2 years for mild, moderate and squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 96%